Error estimation and adaptivity for nonlinear FE analysis - Huerta, Antonio; Rodríguez-Ferran, Antonio; Díez, Pedro (Zielona Góra: Uniwersytet Zielonogórski)
An adaptive strategy for nonlinear finite-element analysis, based on the combination of error estimation and h-remeshing, is presented. Its two main ingredients are a residual-type error estimator and an unstructured quadrilateral mesh generator. The error estimator is based on simple local computations over the elements and the so-called patches.
Keywords: finite elements; error estimation; adaptivity; nonlinearity; quality of FE solutions; damage models